HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT KEJADIAN DEPRESI PADA REMAJA SELAMA MASA PANDEMI COVID-19 DI SMA NEGERI 11 MAKASSAR - Nanda Lola Rahmatia; Fhirastika Annisha Helvian; Trisnawaty (State Islamic University of Sunan Ampel, 2022)
During adolescence, the phases of development and emotional change occur in most teenagers, and a parenting style plays a major role and a significant impact in the process of making adolescents mature and possess decent behaviour. The purpose of this study was to investigate the relationship between the parenting style and the depression of adolescents during the COVID-19 pandemic at SMAN 11 of Makassar. The methodological approach used in this research was an analytic correlation method by using a cross-sectional design. The population of this study was all students of class XII with a total sample of 169 students selected by using a purposive sampling technique. Based on the analysis of the research data, this study indicated that 72 students (42.6%) of SMAN 11 of Makassar were considered to be not depressed. Moreover, 39 students (23.1%) showed moderate depression, and 29 students (17.2%) were indicated to get little depression. In contrast, 19 students (11.2%) had severe depression, while the rest 10 students (5.9%) had very severe depression. Meanwhile, based on the results of the research on parenting applied by parents with the category of authoritative parenting type as many as 57 students (33.7%), authoritarian parenting type as many as 52 students (30.8%), neglected parenting type as many as 31 students (18, 3%), the type of permissive parenting were 29 students (17.2%). The results of the statistical calculations using the Pearson-Chi-Square test found that the relationship between the parenting style and the students' depression level was obtained with a p-value <0.05.